THE ABILITY OF THE SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UR IN DETERMINING THEME AND PLOT IN SHORT STORIES - Defi Anggraini; Erni '; Syafri. K ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed to describe the level of the students’ ability at English Study Program of FKIP of University of Riau in determining theme and plot in reading short stories. The design of this research is descriptive research, which has one variable to observe. This research used quantitative data, where the students were assessed by their score. To determine the sample, this research used cluster random sampling technique. The population of this research was the sixth semester students of English study program of FKIP of Riau University in the academic year 2016/2017. The total number of population was 70 students. There were 25 sixth semester students chosen as the samples of this research. The instruments of the research were 30 multiple choice questions. In collecting the data this research used written test. There were 10 questions given to the students in each short stories and had to be done in 90 minutes. All of the short stories are taken from a number of short stories. Based on the result of the research, there was 1 student (4%) in excellent ability level, 6 students (24%) who were in good ability level, 13 students (52%) who were in mediocre level. Then, there were 3 students (12%) who were in poor level and 2 students (8%) who were in very poor level. In other words, the sixth semester students of English study program of FKIP of University of Riau ability level are categorized in mediocre level. Moreover, from the result found, the students’ ability is in mediocre level with the mean score 53.54.Key words: student, ability, short story, theme, plot